MicroRNA-148 as a negative regulator of the common TLR adaptor mediates inflammatory response in teleost fish - Qing Chu (Nature Portfolio, 2017)
Abstract MicroRNAs are small endogenous noncoding RNAs implicating in the regulation of diverse biological processes, including proliferation, differentiation, cancer, apoptosis, and viral infections. MicroRNAs regulate gene expression by either mRNA degradation or inhibition of protein translation. Although microRNAs have emerged as important controller involved in regulation of inflammatory response, the microRNA-mediated regulatory mechanism remains less clear in teleost. Here, we report that miR-148 targets MyD88 and down-regulates its expression by inhibition protein translation rather than degradation mRNA in miiuy croaker. Additionally, we found that miR-148 was significantly upregulated in miiuy croaker after treated with Vibro harveyi, as well as LPS. Overexpression of miR-148 inhibited LPS-induced inflammatory cytokines production, such as IL-6 and IL-1β, which then avoid excessive inflammation response. miR-148 has also been identified to suppress NF-κB pathway through targeting and repressing MyD88 expression. Taken together, our findings indicate that miR-148 participates in bacteria-induced inflammatory response and act as a negative regulator for MyD88-mediated NF-κB signaling, which may clarify the mechanism of microRNAs for avoiding excessive inflammation in teleost fish.